Admission Circulating Cell-Free DNA Levels as a Prognostic Factor in Pediatric Burns. (8th June 2022) - Halpern, D.; Cohen, A.; Sharon, N.; Krieger, Y.; Silberstein, E.; Michael, T.; Douvdevani, A.; Shoham, Y.
Abstract : Background. Burn injuries in children are a major physical and psychological trauma, often a severe condition with long-term consequences. Current methods of assessing the extent of burn injuries on admission are inaccurate. Circulating cell-free DNA (cfDNA) is a potential marker of tissue damage that may be useful in burn care. Objective. To explore the use of cfDNA admission levels as a prognostic marker of pediatric burn severity and outcome. Methods. cfDNA levels of 38 pediatric burn patients (otherwise healthy) and 12 matched pediatric controls (minor elective surgery patients) admitted to our center were quantified by a direct fluorometric assay. Results. We found significantly higher admission cfDNA levels in the patient group (median 724 ng/ml, range 44-4405), compared to the control group (median 423 ng/ml, range 206-970, Mann–Whitney, P = 0.03 ) and a significant difference between cfDNA levels of partial-thickness burns (median 590 ng/ml, range 44-2909) and full-thickness burns (median 2394 ng/ml, range 528-4405, Mann–Whitney, P = 0.01 ). We also found significant correlations between cfDNA levels and hospitalization duration (Spearman, R = 0.42, P < 0.01 ) and undergoing surgical procedures (Spearman, R = 0.40, P < 0.01 ). PICU admission did not correlate to cfDNA levels (Spearman, R = 0.14, P = NS ). Discussion. Admission cfDNA levels may be a valuable objective tool for assessing the severity of pediatric burn injuries on admission, including correlations with the length of hospitalization and surgical burden. Conclusion. Admission cfDNA levels may be a promising novel pediatric burn assessment method. Further investigation of cfDNA levels in healthy children standardized to age and larger cohorts are needed to establish cfDNA as a valuable prognostic factor for pediatric burn injury.